ASSESSMENT OF THE NUTRITIONAL AND MICROBIOLOGICAL QUALITY OF VENDED TIGER NUT (Cyperus esculentus) DRINK IN CHOBA, RIVERS STATE, NIGERIA - Eruteya, Onoriode Christian; Mmonu, J. C.; Jonathan, F. C. (FUDMA JOURNAL OF SCIENCES, 2024)
The study was aimed at determining the nutritional and microbiological quality of tiger nut milk (Kunun-aya) sold by three vendors for a three-week period in Choba, Rivers State, Nigeria. Standard methods were employed in determining the proximate, mineral composition, total heterotrophic bacterial counts and presence of Staphylococcus and Escherichia species. Moisture content was consistently highest, ranging from 78.04±2.24 to 87.34±1.24, followed by carbohydrate (7.41±1.88 to 15.14±2.33) and the least was ash (0.11±0.03 to 0.26±0.14). The most abundant of the five minerals was potassium (K) with values ranging from 837.98±15.26 to 931.43±33.30, followed by sodium (Na) with values ranging from 587.39±15.58 to 663.78±34.65 and the least was iron (Fe) with values ranging from 8.50±3.57 to 13.44±3.47. Microbial counts results reveal the following for total heterotrophic bacteria (1.4 to 9.5×107 cfu/ml), Staphylococcus (1.6×103 to 5.5×104 cfu/ml) and Escherichia spp. (0 to 5×103 cfu/ml). The results obtained in this study has revealed the presence of valuable nutrient needed for healthy living as well as high microbial loads and presence of etiologic agents of human infections in vended tiger-nut milk sold in Choba. This underscores the need for the milk to be aseptically prepared to forestall the transmission of pathogenic bacteria to consumers.